2018
DOI: 10.1186/s12991-018-0185-3
|View full text |Cite
|
Sign up to set email alerts
|

The long-term outcome of patients with heroin use disorder/dual disorder (chronic psychosis) after admission to enhanced methadone maintenance

Abstract: BackgroundOver-standard methadone doses are generally needed in the treatment of heroin use disorder (HUD) patients that display concomitant high-severity psychopathological symptomatology. A flexible dosing regimen may lead to higher retention rates in dual disorder (DD), as we demonstrated in bipolar 1 HUD patients, leading to outcomes that are as satisfactory as those of HUD patients without high-severity psychopathological symptomatology.ObjectiveThis study aimed to compare the long-term outcomes of treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
0
11
2
2
Order By: Relevance
“…There is little other literature on outcomes of MMT in patients with psychotic disorders with just 2 small studies specifically examining outcomes in this population. 16 , 17 A retrospective study of 206 participants with a variety of psychiatric diagnoses, including 13 individuals with a diagnosis of schizophrenia-examined retention in treatment. 16 At 12 months, only 1/13 (7.7%) people with schizophrenia remained in treatment, a retention rate markedly lower than the rate of retention among all other psychiatric comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is little other literature on outcomes of MMT in patients with psychotic disorders with just 2 small studies specifically examining outcomes in this population. 16 , 17 A retrospective study of 206 participants with a variety of psychiatric diagnoses, including 13 individuals with a diagnosis of schizophrenia-examined retention in treatment. 16 At 12 months, only 1/13 (7.7%) people with schizophrenia remained in treatment, a retention rate markedly lower than the rate of retention among all other psychiatric comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“… 14 In fact, individuals with psychosis are often excluded from controlled trials of opioid substitution therapy. 15 , 16 The existing literature on outcomes in opioid substitution therapy in individuals with comorbid psychotic disorders includes a limited number of small observational studies, 16 , 17 one that identified a markedly lower rate of retention in treatment for individuals with schizophrenia 16 and the other that found no significant difference in treatment retention. 17 Integrated treatment is considered to be the gold standard for individuals with schizophrenia and substance use disorders, though treatment is rarely offered in this way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Achieving control of mood instability or psychotic episodes is the next step. It should, eventually, be followed by a preventive strategy to counter residual cravings and breakthrough episodes of mood disorders or psychotic episodes by using long-term pharmacological maintenance with a double target [53,54]. Relapse prevention must never be understood as complete extinction, but as a trend towards a lower grade of severity, a reduction in frequency, while successfully delaying the possible occurrence of a relapse [55,56].…”
Section: Towards a Hierarchical Approach To Dual Disorder Treatmentmentioning
confidence: 99%
“…Several studied are been performed for the management of psychosis and opioid use. Drugs such as buprenorphines and olanazepines are generally used in the management of opioid-induced psychosis (Maremmani et al, 2018). For acute opioid withdrawal, benzodiazepenes are generally used, but it is recommended only for short term use only (Gaur et al, 2019).…”
Section: Management Of Opioid-induced Psychiatric Disordersmentioning
confidence: 99%